Konsep Etika Sosial dalam Pandangan Ketuhanan Jean-Luc Marion di Era Postmodern - Taneo, Rolin Ferdilianto Sandelgus; Ludji, Irene; Y. M. Lattu, Izak (Studia Philosophica et Theologica, 2023)
The problem of human trafficking in East Nusa Tenggara is a humanitarian issue but also a theological problem. Therefore, the attitude of the church and all members of the NTT community is also a determinant for breaking the human trafficking chain in NTT. Therefore, this paper is intended to clearly state and at the same time focus on how the church’s contribution in NTT is actually in participating in solving this problem. This paper, will examine more of the existing literature. Then, the search results will be elaborated in order to get a link to the problem written, and offer solutions to be noticed and followed up.